Investigation of convective heat transfer performance in nanochannels with fractal Cantor structures. (June 2021) - Wang, Man; Sun, Haiyi; Cheng, Lin
Highlights: Fractal Cantor structures can enhance the convective heat transfer of nanochannels. Fractal structures increase heat transfer areas and low potential energy regions. The fractal nanochannel of n  = 3 has the optimal thermal and flow characteristics. Narrowest gaps in fractal structure of n  = 3 induce the local hydrophobic effect. Abstract: The micro/nanochannel cooling technology is a promising and flourishing technique of thermal management to dissipate the heat of electronic devices. Here, we apply fractal Cantor structures to construct the self-affine rough surface of the nanochannel and investigate the effect of the fractal Cantor surface on the convective heat transfer performance in nanochannels by using molecular dynamics simulation. We first find out that fractal structures can accelerate the temperature development of the fluid and improve the convective heat transfer of nanochannels in comparison with those of smooth surfaces. With the increase of the fractal number ( n ) and the surface wettability, both the heat transfer and flow resistance further increase. The largest comprehensive convective heat transfer performance indicator is obtained at n  = 3. The results show that the expansion of low potential energy regions along with the increasing fractal number makes more near-wall fluid atoms gather at the wall-fluid interface to act as "phonon bridge" to promote the convective heat transfer in nanochannels. Meanwhile, the generation of narrowest gaps in the fractal structure of n  = 3 induces the local hydrophobic effect, which can ameliorate comprehensive thermal and flow characteristics of nanochannels.